Jejak-Jejak Psikologis dalam Tulisan Tangan Bung Karno - Wildan Insan Fauzi; Iing Yulianti (Jurnal Sejarah Citra Lekha, 2022)
Reading a person's character through handwriting can be learned through a science called "Graphology". The main limitation of this research problem is "how to analyze the character of Sukarno using a graphological approach and a historical approach?” The stages of handwriting analysis are an intuitive process, using guidelines, and integrating the first and second stages. The historical method is used to obtain a description of the character of a historical figure for comparison with the results of the graphological analysis. The results showed that the graphology and historical studies did not contradict and instead clarified each other. Historical facts further strengthen the results of the graphological analysis. However, there are some contradictions in historical and graphological findings that require in-depth analysis. In Sukarno’ study, contradictions include the social spirit and dominant character as well as efforts to maintain distance from others, leadership from the aspect of technical organizing, and emotional stability or instability.